The Cocoki Board as a Development of Javanese Script Flashcard Learning Media for Grade VII Students at SMP Negeri 2 Sidoharjo Sragen - Mistia Oktavia Santi; Tukiyo; Krisna Pebryawan (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2025)
This research is about learning media which has quite important meaning in the learning process, especially learning Javanese. Learning will be better assisted by presenting creative and innovative learning media. This research discusses flashcard learning media with the development of the